Technologies and Leadership: Revolutionizing Management Control in African SMEs - (:unkn) unknown (My University, 2024)
This article examines how the integration of modern technologies and leadership qualities influence the structuring of management control (MC) in SMEs in Sub-Saharan Africa. By analyzing fifteen SMEs, the study identifies three types of structuring processes (progressive, stationary, blocked) and highlights the crucial role of the educational background, behavior, and involvement of leaders. The adoption of advanced technologies, such as ERP/CRM systems, is essential for revolutionizing management practices. The findings provide recommendations for improving leadership practices and the competitiveness of SMEs.
Keywords: African Research